Optimasi Penditribusian Air Minum Kemasan Menggunakan Metode Improved Zero Poin - Pane, Peronika (Journal Global Technology Computer, 2024)
Distribution is the process of distributing goods from producers to consumers who need them. Distribution is an important factor for companies to be able to deliver products quickly and precisely to consumers. The accuracy of product delivery must have a basis for scheduling and determining the route that must be precise, so that the product is received in good condition and in accordance with the time limit specified by the customer. PT. Hokkan Deltapack Industri Tanjung Morawa is required to have the ability to manage the distribution system properly. In reality, the company has not carried out proper distribution scheduling planning so that the company has not been able to control the condition of the inventory in the warehouse. This often happens at certain times such as the month of Ramadan, Eid, Christmas and New Year. In addition, the company also does not use a method in distributing products, the company still uses tenders so that the company does not have a definite cost for each shipment per period. The distribution process in one product shipment is only carried out to one distributor with a different number of shipments each time it is transported. Each distributor has a different route causing a longer distance. The longer distance causes the time and costs required to be greater. Based on the problems above, the company needs a distribution schedule and determination of distribution routes appropriately to reduce waste in terms of time, distance, and energy and to obtain more efficient transportation costs. Therefore, it is necessary to plan product distribution using the Improved Zero Point Method. (IZPM) Improved Zero Point is a very useful method for solving all types of transportation problems, this method provides optimal solutions without the help of any other modification methods.